Analysis of the Potential for Developing Community Participation-Based Sports MSMEs in Sungai Ulas Village (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to explore the potential for developing sports-based Micro, Small, and Medium Enterprises (MSMEs) in Sungai Ulas Village based on community sports participation patterns. This research employs a qualitative exploratory approach with a purposive sampling technique. Data were collected through in-depth interviews with 10 informants, consisting of sports enthusiasts, school principals, and community members. Data analysis was conducted using NVivo 12 Pro software with a thematic coding approach covering four main themes: community interest and participation in sports, purchasing patterns of sports equipment, accessibility constraints to sports products, and perspectives on sports MSME development. The findings indicate high community interest in sports activities, particularly volleyball and football, involving various age groups from youth to housewives. However, accessibility constraints to sports equipment remain a major challenge, as residents must travel to the district capital or purchase online with high shipping costs. The community shows positive attitudes toward local sports MSME development, believing it would facilitate access and boost the village economy. Sports MSME development has significant potential if managed strategically by considering community characteristics and needs. This requires collaboration between the village government, local entrepreneurs, and sports communities to build a village-based sports economy ecosystem.